The Roles of External Auditors on Financial Information Quality - Chnar Abdullah Rashid; Naji Afrasyaw Fatah (Eurasian Journal of Management & Social Sciences)
The aim of this study is to explain and assess the reasons why auditors devote time and resources to auditing a company’s financial statements. In addition, attempts are made to explain the reasons for gathering further audit evidence in specific areas of the entity’s reporting and operations. In addition, the roles of external auditors are critically assessed. Thus, the hypothesis has been made in which external auditor has a significant effect on financial information quality. Moreover, we hypothesize that external auditors can rely on the internal audit function but with further audit evidence. For testing the hypotheses, a questionnaire has distributed among internal and external auditors in public and private companies and organizations. The findings suggest that external auditors have a significant effect on financial information quality. Furthermore, external auditors cannot rely only on the internal auditors, instead, he/she must gather audit evidence to give his/her opinion regarding a true and fair view of the company’s financial statement.